Mobbing on the workplace - Vuković Drenka (Temida, 2006)
A phenomenon of mobbing has become very popular in mass-media, everyday speech, and scientific literature. In recent decades of the previous century, the systematic researches of the problem of mobbing on the workplace have been intensified. Most often, they refer to the research conducted by Henz Leymann, who precisely defined the term, determined the basic features, phases and consequences of mobbing, and also founded a clinic for giving support to the victims of mobbing. Further research of the problem resulted in a significant number of studies regarding the prevalence of the phenomenon, risk groups, motives and final aims of mobbing. Multidisciplinary approach to the problem encouraged the development of programs of aid and support to the victims, and also a number of regulations sanctioning the mobbing on the work-place were enacted. The paper is structured within the thematic parts, in order to define the term, and determine the procedures, characteristics of mobbing, prevalence of the phenomenon and its consequences. The used results of the empirical research confirm the national specifics and general characteristics of this problem in the European countries, while the data for Serbia are missing. .